EXTENDING HINGE EPISTEMOLOGY (Anthem studies in Wittgenstein, 2022)
Hinge Epistemology is rapidly becoming one of the most exciting areas of epistemology and Wittgenstein studies. In connecting these two fields it brings a revived energy to both, opening them up to fresh developments. The essays in this volume extend the subject in terms of both depth and breadth. They present new voices and challenges within hinge epistemology. They explore new applications and directions of hinge epistemology, particularly as it relates to the philosophy of mind, society, ethics, and the history of ideas.